Thickness Analysis of Low Density Polyethylene Plastic as Packaging for White Oyster Mushroom (Pleurotus florida) - Alimul Khakim (Contributions of Central Research Institute for Agriculture, 2021)
The purpose of this study was to study the effect of the thickness of low density polyethylene plastic as a packaging material for White Oyster Mushrooms on the modification of O2 and CO2 gases and the physical changes that occur during storage. P Completely randomized design (CRD) was used to analyze data on changes in the composition of O2 and CO2 and followed by a T test if the analysis of variance showed that different treatments had a significant effect on changes in O2 and CO2 concentrations. The results of the diversity test showed that the treatment of differences in LDPE plastic thickness had a very significant effect on the concentration of O2 and CO2 gases in the plastic packaging. The thickness of LDPE plastic 0.04 mm is the best thickness that is able to maintain the quality of white oyster mushrooms with a texture value of 0.022 mm/g.sec, weight loss of 0.74%, reduction of water content of 1% and an average minimum oxygen concentration in the package of 3.2 % and the maximum concentration of carbon dioxide in the package is 8.2%. The highest decrease in water content at 0.03 mm thickness was 1.3% and the lowest at 0.08 mm thickness was 0.63%. The lowest respiration rate was 21.71 mlCO2/kg/hour which occurred at a thickness of 0.08 mm on the 5th day of storage. If the respiration rate of a commodity can be matched with the permeability of the film on the package, then a favorable passive atmosphere condition can be achieved within the package. This method is commonly known as Modified Atmosphere Packaging (MAP).